Smart Agribusiness through Analysis of Balinese Cattle Fattening Using Alternative Feed in Palembang, Indonesia - Sriati; Maryadi; Saad, Giezandi (Journal of Smart Agriculture and Environmental Technology, 2024)
The development of cattle fattening is one of the efforts to fulfill the increasing demand for meat, in line with the growth of the human population. In addition, cattle fattening also provides significant economic opportunities for farmers and business actors in the livestock sector. One important aspect in this regard is feed management, which can have a major effect on the growth and health of livestock. Therefore, this study aimed to (a) analyze the initial weight of cattle, length of fattening time, daily weight gain, and (b) assess the feed cost, selling price, as well as income before and after fattening. A descriptive qualitative method was used to explain the feasibility of cattle fattening business grouped based on four feeding patterns namely (a) grass, (b) grass and tofu pulp, (c) grass, tofu pulp, and sweet potato skin, as well as (d) grass, tofu pulp, sweet potato skin and molasses in Palembang, Indonesia. Furthermore, purposive sampling was used with 100 cattle as the population, divided into four different diet groups. Data analysis was conducted using mean differences to evaluate the impact of the four feed alternatives on the measured variables. The results showed that there were significant differences in income, with molasses generating the highest income per kilogram (kg) of beef. In the feasibility analysis, molasses showed good feasibility with an R/C Ratio of 1.56, implying that cattle fattening business by applying molasses feed alternative could be considered as a viable investment. The results provided practical insights for cattle fatteners, assisting in decision-makingregarding optimal feed patterns to increase income and business viability.